PENGARUH MOTIVASI DAN KONSEP DIRI TERHADAP KEPUASAN KERJA GURU SMP NEGERI KECAMATAN SAMARINDA UTARA - eka selvi handayani (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
The purposes of the research are to analyze the influence between motivation and self concept toward teachers’ job satisfaction.The Study was conducted at junior high school (SMP Negeri) Kecamatan Samarinda Utara (2012) with 29 teachers’ sample probability sampling. Data collection techniques using structured questionnaires, with three instruments of teacher job satisfaction, motivation and self-concept. Instruments in calibration by using validity and reliability test. Grain validity is calculated by using Pearson Product Moment correlation coefficient while the instrument reliability coefficient is calculated by Alpha Cronbach formula. The results of the research indicate that there are positive influence between (1) motivation (X1) and teachers’ job satisfaction (Y) with contribution 72,30%; (2) self concept (X2) and teachers’ job satisfaction (Y) with contribution 50,40%; (3) Moreover, there is a positive influence between motivation (X1) and self concept (X2) with teachers’ job satisfaction (Y) with contribution 74,30%